1995
DOI: 10.1088/0266-5611/11/3/009
|View full text |Cite
|
Sign up to set email alerts
|

Minimal a priori assignment in a direct method for determining phenomenological coefficients uniquely

Abstract: We identify the coefficients of the transport equation in N dimensions grad c.grad h+c Delta h=d delta h/ delta t+f by solving a differential system of the form grad c+ca=b. The assignment of c at one point only yields a unique solution, found by integration along arbitrary paths. This arbitrariness guarantees a good control of the error, notwithstanding the ill-posedness of the problem. For N=2, the hypotheses allowing for this identification are satisfied when one knows two stationary potentials with non-ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…The idea of using hydraulic head measurements from a variety of steady statē ow conditions has long been suggested [e.g., Scarascia and Ponzini, 1972;Ponzini and Lozej, 1982;Ponzini and Crosta, 1988;Giudici et al, 1995a;and Parravicini et al, 1995]. These authors have shown soundly that the transmissivity may be determined uniquely provided that head measurements under independent¯ow conditions are available.…”
Section: Introductionmentioning
confidence: 99%
“…The idea of using hydraulic head measurements from a variety of steady statē ow conditions has long been suggested [e.g., Scarascia and Ponzini, 1972;Ponzini and Lozej, 1982;Ponzini and Crosta, 1988;Giudici et al, 1995a;and Parravicini et al, 1995]. These authors have shown soundly that the transmissivity may be determined uniquely provided that head measurements under independent¯ow conditions are available.…”
Section: Introductionmentioning
confidence: 99%
“…For confined aquifers in the stationary case, if two sets of data are given, say h 1 and h 2 , the full rank condition means that the gradients ∇h 1 , ∇h 2 of the potentials do not vanish and their equipotential lines do not overlap anywhere. This is fully discuss in [6]. Since linear independence of ∇h 1 , ∇h 2 at a point (x, y) is equivalent to linear independence of h 1 ∇h 1 , h 2 ∇h 2 , the same physical condition implies the full rank condition for unconfined aquifers in the stationary case.…”
Section: The Continuous Inverse Problemmentioning
confidence: 94%
“…Now, let us rewrite equation (6) recalling definition (4) and writing down the dependence upon x explicitly. We have the following system for the first two components of u…”
Section: The Continuous Inverse Problemmentioning
confidence: 99%
See 2 more Smart Citations